2010
DOI: 10.1002/ibd.21247
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal dendritic cells

Abstract: Dendritic cells (DCs) play a key role in discriminating between commensal microorganisms and potentially harmful pathogens and in maintaining the balance between tolerance and active immunity. The regulatory role of DC is of particular importance in the gut where the immune system lies in intimate contact with the highly antigenic external environment. Intestinal DC constantly survey the luminal microenvironment. They act as sentinels, acquiring antigens in peripheral tissues before migrating to secondary lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 255 publications
0
40
0
Order By: Relevance
“…Gut bacteria shape immune homeostasis and influence the generation of regulatory T cells [37]. Antigen-presenting cells within the gut are directly affected [38], with recent evidence suggesting that particular metabolites such as short-chain fatty acids are key players [39, 40]. We have shown that the mice transferred with the MyD88−/−NOD microbiota expressed regulatory immune responses in the gut, with increased IgA and TGFβ as well as a considerable increase in a population of CD8 + CD103 + T cells which have been identified to be a regulatory CD8 population [41].…”
Section: Discussionmentioning
confidence: 99%
“…Gut bacteria shape immune homeostasis and influence the generation of regulatory T cells [37]. Antigen-presenting cells within the gut are directly affected [38], with recent evidence suggesting that particular metabolites such as short-chain fatty acids are key players [39, 40]. We have shown that the mice transferred with the MyD88−/−NOD microbiota expressed regulatory immune responses in the gut, with increased IgA and TGFβ as well as a considerable increase in a population of CD8 + CD103 + T cells which have been identified to be a regulatory CD8 population [41].…”
Section: Discussionmentioning
confidence: 99%
“…CD103 + DC are derived exclusively from pre-DC under the control of fms-like tyrosine kinase 3 (Flt3) ligand and its receptor Flt3, whereas CD103 − DC are a heterogeneous population dependent on both Flt3 and macrophage colony-stimulating factor receptor (MCSF-R) (79). The two DC subsets have different functions in the intestine and lung (8, 9, 11, 12). Lamina propria CX3CR1 + CD103 − DC sample intestinal antigens by projecting dendrites through the epithelial cell layer and into the lumen, may serve as a first line of defense by phagocytosing and killing bacteria (1316).…”
Section: Introductionmentioning
confidence: 99%
“…CD103 + LP DCs preferentially promote the differentiation of Treg cells 12, 13 , whereas CX 3 CR1 + LP DCs and microphages can induce Th1 and Th17 development in the gut. To determine whether there were altered mucosal CD4 + T cell subsets upon deletion of gp96 from CD11c + APCs, we isolated cLP from KO mice and WT littermates, followed by examination of T cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…CD103 + intestinal DCs consist of CD103 + CD11b + DCs controlled by the transcription factors IRF4 and Notch2 810 and CD103 + CD11b − DCs that require BATF3 and IRF8 for their respective development 11 . CD103 + DCs preferentially promote the differentiation of Foxp3 + regulatory T (Treg) cells to maintain tolerance 1214 . In addition, a recent study showed that CD103 + CD11b − DCs are required for peripheral Treg cell induction during dietary antigen exposure 2 .…”
Section: Introductionmentioning
confidence: 99%